ANALISIS DAN PERANCANGAN SISTEM ADMINISTRASI PASANG BARU INDIHOME DI PT. TELKOM INDONESIA PLASA TANJUNGBALAI - Helmi Fauzi Siregar; Nilfa Sari ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - In an agency / company, also wants to have a change that can support the progress of the company. Where changes can help work employees more quickly and effectively. especially PT. Telkom Indonesia Plaza Tanjungbalai of course also requires changes to information to streamline and streamline administrative processes in it. Management and processing of data carried out using the system still shows some problems that exist in the system. Therefore, it is necessary to change information systems that are able to manage and process data effectively and efficiently so that there is good computerization of data. In this training will describe the products produced at each stage of the analysis and design of the administration system of the new indihome at PT. Telkom Indonesia Plaza Tanjungbalai. Analysis and design of an indihome new administration system at PT. Telkom Indonesia Plaza Tanjungbalai is complete and detailed. It is expected that the results of this practical work can answer the difficulties that are often faced by customers so that they can be far more efficient and effective.   Keywords - Administration System, Data Processing, Indihome New Install